Development, Validation and Use of Students’ Evaluation of Teaching Effectiveness Scale in Colleges of Education in Nigeria (2013)
Student‟s evaluation of lecturers‟ teaching effectiveness at the tertiary level of education in Nigeria is being advocated by educators. While universities are currently evolving the modalities of evaluating lecturers‟ teaching effectiveness by students, colleges of education recorded little or no attempt in this respect. Hence, this study developed, validated and used the Students' Evaluation of Teaching Effectiveness Scale in the College of Education (SETES-CE) to measure specific and observable classroom behaviours of lecturers. This study adopted a survey design. Purposive sampling was used to select four colleges in the south-west, Nigeria and 160 students per college selected from year 2 and 3 while stratified sampling was used to select schools and courses. A total of 640 students and 24 lecturers participated in the validation. The SETES-CE (r = 0.72) which consists of four components namely: classroom interaction (r = 0.72), evaluation (r = 0.72), personality (r = 0.72) and preparation (r = 0.72) was used by a sample of 1600 students to evaluate teaching effectiveness. Eight research questions guided the study. Data was analysed using descriptive statistics, t-test, ANOVA and factor analysis. The Average Factor Loading (AFL), Average Communality Value (ACV) and Initial Eigen Value (IEV) of each component of SETES-CE are: classroom interaction (AFL= 0.44, ACV=0.60, IEV=3.61); evaluation (AFL= 0.46, ACV=0.60, IEV=2.64); personality (AFL= 0.45, ACV=0.60, IEV=2.34) and preparation (AFL= 0.44, ACV=0.61, IEV=2.27). Students‟ ratings for SETES-CE varies accordingly for: classroom interaction (152.60 - 156.38); evaluation (52.65 - 53.32); personality (57.04 - 57.96) and preparation (32.88 - 32.93). There was a significant difference in the male and female students‟ ratings of their lecturers‟ personality (t=2.67, df: 1583, p < .05). There exists a significant mean difference in classroom interaction (F (4, 1595) = 6. 41; p < .05) and personality (F (4, 1580) = 3.03; p < .05) of the lecturers rated. For classroom interaction, age (F(12, 1587) =2.24, p<.005), course of study (F(19, 1580) =3.54, p < .05) and year of study (t=-2.82; df: 1598, p < .05) of the students significantly influenced the rating of their lecturers, while age (F (12, 1576) =1.79, p < .05 and course of study (F(19, 1569) =2.25, p <.05) significantly influenced the ratings of their lecturers‟ evaluation, whereas students‟ year of study did not. Only course of study of the students significantly influenced the way they rated their lecturers‟ personality (F (19, 1565) =1.67, p < .05), while both age and year of study did not show significant differences in lecturers‟ personality. In terms of preparation, lecturers‟ rank (F (6, 1578) =2.87: p < .05) and years of experience (F (11, 1573) = 1.83: p < .05) significantly influenced their teaching effectiveness. Students, especially in the colleges of education can be relied upon to evaluate their lecturers‟ teaching effectiveness. Students‟ variables like course and year of study influence their pattern of ratings. The use of SETES-CE could be considered for adoption in the evaluation of teaching effectiveness of lecturers in Colleges of Education in Nigeria